2012
DOI: 10.4236/ampc.2012.21007
|View full text |Cite
|
Sign up to set email alerts
|

Third Order Optical Nonlinearities of C<sub>450</sub> Doped Polymer Thin Film Investigated by the Z-Scan

Abstract: In the present work, z-scan technique was used to study the nonlinear properties, represented by nonlinear refractive index and nonlinear absorption coefficient for Coumarin 450 (C<sub>450</sub>) doped PMMA as a function of concentration for two different solvents. The results show change of the effect from self-focusing to self-defocusing in closed aperture z-can (or change of the effect from two photon absorption to saturable absorption in open aperture z-scan), when the sample dissolved in low v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Organic dyes possessing π -conjugated bonds in the structural backbone are good optical absorbers and exhibit strong optical nonlinearity [8]. Structural modification of dyes results in a shift of their absorption bands to a longer wavelength region and expansion of the existing photonic applications [9]. The large delocalization of π-electrons enhances the nonlinear optical properties of the dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Organic dyes possessing π -conjugated bonds in the structural backbone are good optical absorbers and exhibit strong optical nonlinearity [8]. Structural modification of dyes results in a shift of their absorption bands to a longer wavelength region and expansion of the existing photonic applications [9]. The large delocalization of π-electrons enhances the nonlinear optical properties of the dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the measurements are performed at room temperature. These finding were illustrated in figure (4). From these Figures we can observed that absorption spectrum of coumarin (334) solution has a wide peak over wavelengths from 328 nm to 530 nm.…”
Section: Resultsmentioning
confidence: 53%
“…Thus, Coumarin dyes can be used to cover a large adjustable range of (420 to 580 nm). Some of the most effective laser sources employ coumarin dye [3][4][5]. These compounds are dissolved in an organic solvent and used in dye lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of saturation absorption relates to the formation of molecules in the excited state, which may return directly back to the ground state, Therefore, the focal point of the beam reduces, revealing a high transmittance. It is a crucial component for laser pulse compression applications [61] …”
Section: Resultsmentioning
confidence: 99%